Magnetic resonance imaging predicts the days lost from training and competition: evaluation of 56 indirect muscle injuries in professional football players - Coppola, L.; Canonico, R.; De Luca, G.; Zappia, M.; Bisciotti, G. N.; Rusconi, G.; Barillaro, A.; Di Pietto, F. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Lower limb muscle injuries have a strong impact in training and official competitions stoppage for professional football players. This study aimed to explore the relationship between oedema-like changes found on magnetic resonance imaging (MRI) in acute indirect thigh injuries muscles and the time required for the athlete to return to individual training - "return to training" (RTT) and for full availability for official competitions - "return to play" (RTP). METHODS: Professional football players from 2017/2018 to 2021/2022 seasons top league team with clinical and ultrasound (US) diagnosis of acute hamstrings or quadriceps muscle injury, confirmed on 48/72h subsequent MRI, were included. MRI images were retrospectively re-evaluated. MRI parameters evaluated were cross-sectional area (CSA), cranio-caudal extension (CCE), distance to nearest insertion (DI) and volume (V). Univariate and multivariate analysis was performed to find factors related to RTT, RTP, and episodes of reinjuries. RESULTS: Thirty-four first traumatic muscle injuries met the inclusion criteria. The mean time to RTT and RTP was 22 (4-49) and 25 (4-55) days, respectively. CCE and V resulted as independent predictive MRI variables for the time to RTT (P=0.012) and RTP (P=0.02), respectively. Thresholds of CCE=11.31 cm and V =19.5cc can predict a time to RTT=22 days (Odds Ratio [OR] 9.5) and RTP=25 days (OR 4.583), respectively. CONCLUSIONS: The decision on the time required for RTP is based on clinic and imaging evaluation; CCE and V of the MRI oedema-like changes help to define the prognosis of the injury.